Forever Young: mission impossible? - Cucinotta, Domenico (Acta Biomedica Atenei Parmensis, 2024)
Despite an increase in life span over the last century, most people spend the extra years in poor health. Undoubtedly, older patients will rise to the overall majority of patients accessing social and healthcare systems unprepared to respond to special and complex demands. The future has to undergo a significant transformation, emphasizing a healthier and more active aging process. Looking ahead, prioritizing "health span", not life span. will help us make the most of the opportunities that come with longer lives and practical approaches to increase the number of healthy years (healthy ageing medicine and timely intervention to counteract pathological senescence), highlighting the positive impact a healthier population can have on both the economy and society.